2022
DOI: 10.1186/s12888-022-04469-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and related factors among Syrian breast cancer patients: a cross-sectional study

Abstract: Introduction Breast cancer represents a traumatic experience with a psychological burden. The prevalence of psychological distress (which include depression and anxiety) among breast cancer patients is estimated to be 15 to 54%, but studies have shown that applying some psychological treatments has contributed to decreasing depression and anxiety. So, it is crucial to diagnose and treat patients with the appropriate means. After reviewing the literature, no studies discussed depression and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…We also observed that older patients were significantly more likely to exhibit depressive symptoms compared with younger patients. This contradicts findings from a study conducted in Syria which showed that younger women with BC suffered more frequently from anxiety and depressive symptoms compared with older women 35. Indeed, younger women in Oman are reportedly more likely to exhibit anxiety symptoms because of their fear of adverse effects affecting their perceived attractiveness and femininity as a result of the side effects of cancer treatment 36.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We also observed that older patients were significantly more likely to exhibit depressive symptoms compared with younger patients. This contradicts findings from a study conducted in Syria which showed that younger women with BC suffered more frequently from anxiety and depressive symptoms compared with older women 35. Indeed, younger women in Oman are reportedly more likely to exhibit anxiety symptoms because of their fear of adverse effects affecting their perceived attractiveness and femininity as a result of the side effects of cancer treatment 36.…”
Section: Discussionmentioning
confidence: 78%
“…However, older people with BC in Germany were found to be 1.2-times more likely to experience both depressive and anxiety symptoms compared with younger patients 37. In general, older individuals with BC may be more likely to report depressive symptoms compared with younger individuals because of lack of energy, increased sleep disturbances, decreased interest in activity and the coexistence of other conditions, such as cardiovascular disease, stroke, diabetes and hearing or visual impairments, all of which are more frequent in older age 31 35…”
Section: Discussionmentioning
confidence: 99%
“…While this discrepancy could partly be attributed to the differential impact of the earthquake on these cities-with Aleppo experiencing more severe effects. 10,23 it is also necessary to consider other contributing factors. These may include, but are not limited to, pre-existing infrastructure, availability of resources, and the level of social support systems in place.…”
Section: Discussionmentioning
confidence: 99%
“…These may include, but are not limited to, pre-existing infrastructure, availability of resources, and the level of social support systems in place. 23 Such factors could influence the mental health outcomes of healthcare providers and highlight the need for interventions tailored to the unique challenges faced in each location.…”
Section: Discussionmentioning
confidence: 99%
“…It was also higher than primary studies conducted in India, 18 Malaysia, 40 Jordan, 41 and Syria. 42 The discrepancy might mainly be due to the difference in the countries’ income level. The present review was mainly on the SSA countries where there is low healthcare expenditure, poor health care infrastructure, high cost of medication, transportation and accommodation.…”
Section: Discussionmentioning
confidence: 99%